Utilization of wax residue as compatibilizer for asphalt with ground tire rubber/recycled polyethylene blends. (10th January 2020) - Liang, Ming; Sun, Changjun; Yao, Zhanyong; Jiang, Hongguang; Zhang, Jizhe; Ren, Shisong
Graphical abstract: Highlights: A composite modifier was developed by wax residue, crumb rubber and polyethylene. Wax residue enhances storage stability of asphalt with the composite modifier. The proper amount of wax residue improves the low temperature behavior. Wax residue is a good compatibilizer for asphalt with crumb rubber and polyethylene. Abstract: Wax residue (WR) is a by-product of Fischer-tropsch synthesis (FTS), which is currently disposed as common solid waste and utilized with low value-added. Meanwhile, ground tire rubber (GTR) and recycled polyethylene (RPE) as low-cost modifiers for asphalt modification have been focused. This study attempts to evaluate the feasibility of utilization of WR as compatibilizer for asphalt modified with GTR/RPE. To that end, GTR, RPE and WR were mixed through a direct melt compounding in a co-rotating twin screw extruder, which were further used to modify asphalt. The effects of GTR/RPE ratio and WR were assessed by evaluating performance of the modified asphalt. The results indicated that GTR/RPE blends contribute to improving high-temperature performance of the modified asphalt. Decreasing ratio of RPE to GTR leads to the reduced high temperature performance but enhanced low temperature performance. The incorporation of WR impairs the high temperature performance of asphalt with GTR/RPE, but the resulting asphalt shows better high temperature performance than commercial SBS modified asphalt. The proper amount of WR improves the low temperature behavior of the modified asphalt. WR improves the fatigue performance of asphalt with GTR/RPE. More importantly, WR enhances storage stability and compatibility of asphalt with GTR/RPE. The degree of dispersion of the modifier is improved with the increase of WR, which verifies the enhancement of compatibility. These results demonstrated that WR is a good stabilizer for asphalt modified with GTR/RPE. Moreover, GTR/RPE/WR additive is effective for the reduction of energy consumption, CO2 emissions and cost in asphalt production.